Negotiating household heat: thermal labor, energy justice, and women’s health in Nepal’s Madhesh Province - Animesh Ghimire; Mohan Das Manandhar; Sarita Karki; Karuna Bajracharya (Frontiers in Public Health, 2025)
IntroductionHousehold cooking with solid fuels exposes women to prolonged indoor heat levels that routinely exceed internationally accepted occupational safety thresholds; yet, this exposure remains largely absent from climate-health analyses. This perspective article introduces the concept of thermal labor—the physiological strain, time cost, and health risks associated with performing domestic work under chronically elevated kitchen temperatures—and argues that such exposure constitutes an overlooked driver of gendered health inequities in Nepal’s Madhesh Province.MethodsEvidence was synthesized from national temperature records, caste-disaggregated census data, spot measurements conducted by the Nepal Health Research Council, and illustrative intervention studies from South Asia and Africa. The policy context was examined through Nepal’s Nationally Determined Contribution, the Clean Cooking Alliance Nepal Country Action Plan, and the National Disaster Risk Legislation.ResultsThe synthesis suggests that accelerated warming in Nepal’s lowlands and caste-linked reliance on biomass fuels result in daily indoor heat exposures. Prior studies associate such exposures with appetite suppression, reduced dietary diversity, and increased time burdens for women who manage household cooking. These established pathways, when considered alongside the socioeconomic profile of Dalit households in Madhesh, indicate a heightened but under-documented risk for this group. Nepal’s existing target of achieving electric cooking adoption in 31.5 percent of households by 2035 offers a practical policy lever for reducing thermal exposure and its associated health and equity impacts.DiscussionPositioning thermal labor as a measurable health determinant broadens the clean-cooking agenda beyond smoke reduction to encompass heat mitigation, nutrition, and gender equity. A balanced approach is proposed: sentinel kitchen-heat surveillance within existing household surveys would establish exposure baselines; thermal-performance criteria in stove-procurement standards could translate policy commitments into verifiable outcomes; and integrating heat indicators into clean-cooking and disaster-risk frameworks would facilitate coordinated action. These steps would convert domestic heat from an invisible stressor into a tractable public health target, illustrating how a single intervention pathway can advance climate, energy, and equity goals.